Proportionality in Private Law - Bauer, Franz; Köhler, Ben (Mohr Siebeck, 2023)
Proportionality is a ubiquitous concept in law. While mostly associated with fundamental rights review, it also plays an important role in private law. In this context, proportionality requirements can be the result of both traditional private law reasoning and the influence of constitutional law. The present volume aims to explore different forms and functions of proportionality in selected private law contexts and jurisdictions. The contributions cover constitutional and theoretical underpinnings of proportionality's role in private law as well as specific examples of how proportionality affects private law in different areas and across different jurisdictions. They include perspectives on German and US-American private, procedural, and constitutional law as well as a special focus on the European dimension.